2017
DOI: 10.1007/s10096-017-3058-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological profile of chronic Burkholderia cepacia complex infections in a cystic fibrosis reference hospital in Brazil

Abstract: Burkholderia sp. infections are extremely complex in cystic fibrosis (CF) patients, especially considering the lack of knowledge regarding its behavior, its relationship with prognosis, as well as its transmissibility and multidrug resistance features. This study evaluated the frequency of chronic infection by Burkholderia, using microbiological and clinical data. Ninety-eight patients with CF attended from July 2011 to April 2014 in a Brazilian reference hospital were included. Antimicrobial activity, molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…These members are most frequently isolated from patients with CF and generally linked to pulmonary deterioration (Coburn et al, 2015), high risk to the host due to multidrug resistance, easy transmissibility, the potential to cause septicemia, and an unpredictable clinical outcome, varying from an asymptomatic infection up to fatal pneumonia known as "cepacia syndrome" (Zlosnik et al, 2015;Hector et al, 2016). A previous study in the same hospital showed patients with good clinical outcomes and favorable options for antibiotic therapy (da Costa Capizzani et al, 2017). Even so, possibly the highly impaired lung functions of these young patients are related to the early presence of very pathogenic bacteria, related to adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These members are most frequently isolated from patients with CF and generally linked to pulmonary deterioration (Coburn et al, 2015), high risk to the host due to multidrug resistance, easy transmissibility, the potential to cause septicemia, and an unpredictable clinical outcome, varying from an asymptomatic infection up to fatal pneumonia known as "cepacia syndrome" (Zlosnik et al, 2015;Hector et al, 2016). A previous study in the same hospital showed patients with good clinical outcomes and favorable options for antibiotic therapy (da Costa Capizzani et al, 2017). Even so, possibly the highly impaired lung functions of these young patients are related to the early presence of very pathogenic bacteria, related to adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%